The palmitoyl-CoA ligase Fum16 is part of a Fusarium verticillioides fumonisin subcluster involved in self-protection - Fabio Gherlone; Katarina Jojić; Ying Huang; Sandra Hoefgen; Vito Valiante; Slavica Janevska (mBio)
ABSTRACT Fusarium verticillioides produces the mycotoxin fumonisin B1 (FB1), which disrupts sphingolipid biosynthesis by inhibiting ceramide synthase and affects the health of plants, animals, and humans. The means by which F. verticillioides protects itself from its own mycotoxin are not completely understood. Some fumonisin (FUM) cluster genes do not contribute to the biosynthesis of the compound, but their function has remained enigmatic. Recently, we showed that FUM17, FUM18, and FUM19 encode two ceramide synthases and an ATP-binding cassette transporter, respectively, which play a role in antagonizing the toxicity mediated by FB1. In the present work, we uncovered functions of two adjacent genes, FUM15 and FUM16. Using homologous and heterologous expression systems, in F. verticillioides and Saccharomyces cerevisiae, respectively, we provide evidence that both contribute to protection against FB1. Our data indicate a potential role for the P450 monooxygenase Fum15 in the modification and detoxification of FB1 since the deletion and overexpression of the respective gene affected extracellular FB1 levels in both hosts. Furthermore, relative quantification of ceramide intermediates and an in vitro enzyme assay revealed that Fum16 is a functional palmitoyl-CoA ligase. It co-localizes together with the ceramide synthase Fum18 to the endoplasmic reticulum, where they contribute to sphingolipid biosynthesis. Thereby, FUM15-19 constitute a subcluster within the FUM biosynthetic gene cluster dedicated to the fungal self-protection against FB1.IMPORTANCEThe study identifies a five-gene FUM subcluster (FUM15-19) in Fusarium verticillioides involved in self-protection against FB1. FUM16 (palmitoyl-CoA ligase), FUM17, and FUM18 (ceramide synthases) enzymatically supplement ceramide biosynthesis, while FUM19 (ATP-binding cassette transporter) acts as a repressor of the FUM cluster. The evolutionary conservation of FUM15 (P450 monooxygenase) in Fusarium and Aspergillus FUM clusters is discussed, and its effect on extracellular FB1 levels in both native (F. verticillioides) and heterologous (Saccharomyces cerevisiae) hosts is highlighted. These findings enhance our understanding of mycotoxin self-protection mechanisms and could inform strategies for predicting biological activity of unknown secondary metabolites, managing mycotoxin contamination, and developing resistant crop cultivars.